Rancang Bangun Sistem Informasi Pendaftaran Siswa Baru Berbasis Web dengan Metode Waterfall pada TK Pertiwi 14 - Gilang Akbar Romadhoni; Susanto Susanto; Titis Handayani (Sekawan Institut, 2026)
The transformation of information technology in the modern era provides significant opportunities to improve the effectiveness of educational administration, particularly in the new student admission process. One form of implementation is a web-based registration system that can automate the online registration flow and minimize data recording errors. Pertiwi 14 Kindergarten currently still uses the conventional registration method through paper forms that require parents to be present in person at the school, potentially causing verification delays, information duplication, and data input errors. This study aims to design and build a web-based new student registration system using the Laravel framework with Laravel Filament support to display a dynamic interface and structured data management. The system development uses the Waterfall model through the stages of needs analysis, design, implementation, testing, and maintenance. Testing results using Black Box Testing show that all system functions run according to specifications without any errors and are able to reduce input errors by up to 100% compared to manual methods. In addition, the registration data verification process is faster with an increase in time efficiency of 70%. The implementation of this system makes a real contribution to improving ease of access, data accuracy, management transparency, and administrative efficiency in the new student admission process at Pertiwi 14 Kindergarten.